Acid-catalyzed conversion of Xylose in 20 solvents: Insight into interactions of the solvents with Xylose, Furfural, and the Acid Catalyst - Hu, Xun; Westerhof, Roel; Dong, Dehua; Wu, Liping; Li, Chun-Zhu (ACS Publications, 2014)
In this study, the acid-catalyzed conversion of xylose to furfural was investigated in 20 solvents ranging from water, alcohol, ketones, furans, ethers, esters, hydrocarbons, and aromatics with the aim to understand their involvement in each step from xylose to furfural. Compared with water, alcohols can stabilize the reactive intermediates, promote the formation of furfural, and slow its degradation with prolonged reaction times. Iso-propanol and 2-butanol can direct the conversion of xylose to levulinic esters via transfer hydrogenation catalyzed by a Brønsted acid catalyst. The other solvents with the carbonyl groups (i.e., ketones) or conjugated π bonds (e.g., furan) react with both xylose and furfural. Either xylose cannot make its way to furfural or furfural cannot survive for long in these solvents. In ethers, hydrocarbons, and aromatics, the formation of furfural is quick but so is the degradation of furfural due to the aprotic properties of these solvents. In an ester like methyl formate, xylose can be converted to furfural selectively and efficiently. Approximately 70% yields of furfural were achieved at 150 °C in a very short time, and more importantly, methyl formate is highly volatile (boiling point: 32 °C). It can be distilled from furfural very easily, making it a promising solvent for furfural production. The solvents also interact with the acidic resin catalysts in varied ways due to their different polarities and molecular size/shape, determining the availability of the acidic sites on the inner surfaces of the catalysts.